Characterization of Suicidal Attempt in Adolescents of the Cumanayagua Municipality - Tamara Montenegro Calderón; Juan Carlos Fernández Wilcapi; Julio César Díaz Marrero; Narciso Águila Rodríguez; Alexis Díaz Brito (Revista Finlay)
Foundation: the World Health Organization has determined that suicide in an important health problem since it is among the first causes of death in all ages. In Cuba and in Cienfuegos a trend to increase has been observed in youngsters. Objective: to characterize the suicidal attempt in adolescent of the Cumanayagua municipality from January 2009 to December 2013. Method: a cross descriptive study was done about the epidemiological behavior according to variables of the suicidal conduct at the Cumanayagua municipality from 2009 to 2013 with a universe of 110 patients. The information was collected by revising cards of compulsory statement and surveys where studied variables were included. The statistical analysis was developed by SSPS program and the results are presented in tables. Results: there were a higher number of suicidal attempts in the female sex, white skin, single and secundary schooling. The predominant model was the ingestion of medications and family, school and personal problems were the triggering factors of suicidal attempt. Conclusion: the multi-causal origin of this phenomenon is undeniable and the personal, interpersonal, and social factors are significant in interaction with circumstance and psycho-social factors which function as unleashing factors.